Moral Values Found in Harry Potter and the Deathly Hallows Novel by J.K. Rowling - Juliani, Asarina Jehan; Tahrun, Tahrun; Yukamana, Hanni (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This research aims to find out moral values in â€œHarry Potter and the Deathly Hallowsâ€ novel. The data of this research were obtained from words, phrases, sentences, and utterances. This research was using a qualitative descriptive method. There were three kinds of collecting the data, they were documentation, interview, and book review from another reader. Five major phases were used for the data analysis: they were data managing, reading, noting, classifying, interpreting, and representing. The results of data analysis shows that moral values in â€œHarry Potter and the Deathly Hallowsâ€ novel are commitment to something greater than oneself; self respect, but with humbleness or respect to others, self-discipline, and acceptance of personal responsibility; respect and caring for others; and caring for other living things and environment.